The Effect of Slow Stroke Back Massage Cutaneus Stimulation on Pain Intensity Osteoarthritis in The Elderly - Anita Gandaria Purba; Arfah May Syara; Luci Riani Br Ginting (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Osteoarthritis (OA) also known as degenerative joint disease is the most common in all forms of arthritis and causes pain and disability in the elderly. This disease is characterized by progressive loss of joint cartilage, synovitis (inflammation of the synovium lining the joints), joint pain, stiffness, and loss of joint movement (Lemone, 2018:1679). Skin stimulation that can be done is Slow-Stroke Back Massage. Proper use of skin stimulation: slow-stroke back massage can reduce pain perception and help reduce muscle tension which can reduce pain intensity, but it can also cause dilation of blood vessels and improve blood circulation in tissues. This activity was carried out at the Lubuk Pakam Health Center in January 2021. The target of this community service is 30 elderly people with osteoarthritis. The method used in this community service is providing education or counseling to patients with Osteoarthritis. The media used are Power point presentation (PPT) and LCD for approximately 90 minutes. To measure the success of the education or counseling provided, knowledge measurement before and after education or counseling was carried out using a questionnaire. Data analysis for bivariate calculations in this study used Pair Samples t-test with the provisions of 0.05. Based on the results of statistical tests using paired sample t-test, p value (= 0.000) < (= 0.05) it can be concluded that the hypothesis in this study is accepted,